The interrelationship of the built environment and walkability - Buose , Gabriellin (Technical and Scientific Journal Green Cities, 2024)
This article investigates the conditions of the built environment that influence urban walkability, essential for public health and quality of life. The study analyzes elements such as sidewalks, lighting, security, building density and proximity to services and green areas. The results show that neighborhoods with adequate infrastructure for pedestrians, such as wide sidewalks, good lighting and proximity to commercial and leisure areas, have higher walkability rates. The perception of safety is crucial, influencing residents’ willingness to walk. Areas with a higher density of walkable services are associated with a greater frequency of walking, suggesting that improvements to the built environment can promote more active and healthy lifestyle habits. The theoretical contributions of the study include confirming the relationship between urban infrastructure and walking behaviors, offering a solid foundation for future research on walkability and urban planning. Social and environmental contributions highlight the importance of urban planning that prioritizes walkability to improve active mobility and promote sustainability. Public policies aimed at this issue can encourage the development of more walkable cities, reducing dependence on motor vehicles and encouraging more active and healthy lifestyles.